2018
DOI: 10.1016/j.npbr.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Season, weather, and suicide–Further evidence for ecological complexity

Abstract: BACKGROUND: Seasonality in suicide is reported worldwide, and peaks in late spring.Despite the potential connection to the weather, associations between meteorological variables and suicide does not explain seasonality. Studies testing for seasonality while controlling for the weather show patterns that are more complex than a straightforward link between spring-like weather and suicide. METHODS: We tested whether seasonality in suicide was due to meteorological variation (hours of sunshine, rainfall, or tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our results showed that suicide numbers peaked in spring in most countries replicating those of previous studies. The most substantiated explanation for the spring peak is the seasonal cycle of bioclimatic factors such as temperature and amount of sunshine (Souêtre et al ., 1987 , 1990 ; Linkowski et al ., 1992 ; Maes et al ., 1993 , 1994 ; Chew and McCleary, 1995 ; Deisenhammer et al ., 2003 ; Lambert et al ., 2003 ; Papadopoulos et al ., 2005 ; Ruuhela et al ., 2009 ; Ajdacic-Gross et al ., 2010 ; Muller et al ., 2011 ; Christodoulou et al ., 2012 ; Vyssoki et al ., 2012 ; Moore et al ., 2018 ). Specifically, levels of serotonin, a neurotransmitter that regulates emotion, are sensitive to weather variability and light exposure, so springtime changes in expression may be associated with increased suicidal behaviour (Brewerton, 1989 ; Praschak-Rieder et al ., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that suicide numbers peaked in spring in most countries replicating those of previous studies. The most substantiated explanation for the spring peak is the seasonal cycle of bioclimatic factors such as temperature and amount of sunshine (Souêtre et al ., 1987 , 1990 ; Linkowski et al ., 1992 ; Maes et al ., 1993 , 1994 ; Chew and McCleary, 1995 ; Deisenhammer et al ., 2003 ; Lambert et al ., 2003 ; Papadopoulos et al ., 2005 ; Ruuhela et al ., 2009 ; Ajdacic-Gross et al ., 2010 ; Muller et al ., 2011 ; Christodoulou et al ., 2012 ; Vyssoki et al ., 2012 ; Moore et al ., 2018 ). Specifically, levels of serotonin, a neurotransmitter that regulates emotion, are sensitive to weather variability and light exposure, so springtime changes in expression may be associated with increased suicidal behaviour (Brewerton, 1989 ; Praschak-Rieder et al ., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the pattern of seasonal suicides has been confirmed in many countries, the mechanisms remain unclear. The most plausible underlying mechanisms for seasonal suicide patterns include seasonal fluctuations of social activities (Souêtre et al ., 1990 ; Maes et al ., 1993 ; Chew and McCleary, 1995 ; Ajdacic-Gross et al ., 2010 ; Christodoulou et al ., 2012 ; Roehner, 2015 ) and bioclimatic factors, such as temperature or amount of sunshine (Souêtre et al ., 1987 , 1990 ; Linkowski et al ., 1992 ; Maes et al ., 1994 ; Deisenhammer et al ., 2003 ; Lambert et al ., 2003 ; Papadopoulos et al ., 2005 ; Ruuhela et al ., 2009 ; Muller et al ., 2011 ; Vyssoki et al ., 2012 ; Moore et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide patterns vary depending on the sex of the victims [33]. In studies by other authors, only one spring peak of suicides was found for men and two peaks, i.e., one in spring and one in autumn, were observed among women [36,37,38,39,40,41]. In England, for example, “middle-aged women with school children often suicide in autumn, at the beginning of the school year…”—which means a shortened time of direct contact with a child [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In studies by other authors, only one spring peak of suicides was found for men and two peaks, i.e., one in spring and one in autumn, were observed among women [36,37,38,39,40,41]. In England, for example, “middle-aged women with school children often suicide in autumn, at the beginning of the school year…”—which means a shortened time of direct contact with a child [36,37]. The impact of sex on the seasonality of suicides was also reported in Hungary, where the spring peak was a consequence of depression-related suicides, especially among men = increased use of prescribed drugs in the population [42].…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal variation in suicides could be a result of changes in patterns of social interaction at the end of winter or a result of meteorological changes. However, Moore et al (2018) reported that the seasonal variation of suicides at the Tay Road Bridge in Scotland (for the period 1968-2017) was found even after controls for temperature and hours of sunshine.…”
mentioning
confidence: 99%